ANALISIS YURIDIS PERTANGGUNGJAWABAN KREDITUR DALAM MASA PENGAWASAN SEBELUM DILELANG MENGALAMI KEHILANGAN SEBAGIAN PROPERTI BARANG JAMINAN (STUDI PADA PT. BANK SUMUT CABANG PEMBANTU MELATI) - HABIBAH NASUTION (PREMISE LAW JURNAL, 2016)
Credit settlement sometimes encounters problems, namely failure in credit payment. In the practice, a creditor requests some collateral for his security in the credit payment. In the practice of the object analyzed in this research, the status of the debtor’s credit is a bad credit. The creditor secured the collateral by means of supervision by planting a signboard on the collateral. However, some of the properties often miss before being auctioned; the collateral was an empty house under the supervision. The debtor filed an objection to the creditor for any compensation, but the creditor refused with an excuse that the missing of some of the properties was not his/her responsibility. Keywords : Creditor, Debtor, supervision, Collateral